Introduction to the Sociology of Development and Development in Social Change - Sri Devi Okta Viani; Elvi Rahmi Syukrina; Yunita Y; Akdila Bulanov (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Development sociology is an activity undertaken by society to transform conditions from less developed to more developed. However, such development activities often do not meet expectations. The results of development often have negative and problematic impacts on other communities. While it is acknowledged that in some cases development does bring positive impacts as expected, many problems and issues also arise as a result of development. The normative concept of development is intended to transform people's lives from poor, less developed conditions to better, more developed, and more modern ones. As sociology first emerged, particularly in America, its orientation was also aimed at improving societies afflicted by severe social problems caused by the rise of industrialization and capitalism. Over its development, sociology has become more than just a normative goal; it has increasingly developed as a neutral, objective, and rational science, thus avoiding normative considerations. As a science, sociology is expected to be able to view and analyze social phenomena (including development phenomena) holistically, comprehensively, and objectively, so that its analysis is clear and unbiased. With such an understanding, the results of sociological analysis can provide significant input for social improvement.